Dr Ain Veterinary Patient Record Information System (DVAS): An Implementation of Role-Based Access Control and Zero Trust Approach - ABDUL SALIM, NUR SYAFIQAH; AB RAHMAN, TS. DR. NURUL HIDAYAH (Applied Information Technology And Computer Science, 2025)
Veterinary Information Management Systems (VIMS) are becoming increasingly essential in modern veterinary practices, streamlining the management of patient records, scheduling, and treatment histories. However, these systems are susceptible to cyberattacks, such as data breaches and unauthorized access attempts. In the event of a security incident, it is crucial to conduct thorough investigations to safeguard sensitive pet health data, and the pet owner's data and ensure the integrity of the veterinary practice. Therefore, this study proposed a Patient Record Information System for Dr Ain Veterinary with Role-Based Access Control and Zero Trust (DVAS), and VIMS developed with Role-Based Access Control and Zero Trust. The prototyping model was adopted to establish the DVAS system, which includes five user modules: doctors, pharmacists, helpdesk staff, admin and pet’s owner. Functional testing results confirm DVAS’s ability to successfully manage the 5 user modules, the database connected to the system, logs functionality, errors in invalid inputs, RBAC and zero trust function. The user acceptance test shows positive feedback and high satisfaction, confirming the effectiveness of DVAS’s features and performance. To sum up, DVAS demonstrates promising features that protect against data breaches and unauthorized access attempts.